Development management - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
An intensive 11-week course in development project planning and management is being offered by the Selly Oak College in the UK, from 29 September to 15 December 2001 and again from 27 April to 13 July 2002. It is designed for people working in NGOs,...